Patho-molecular identification of circulating H9N2 avian influenza virus in Egypt - El Nagar, Eman M.S.; Salem, Heba M.; Gamal, Maha A.N.; El-Saied, Mohamed A. (Journal of Advanced Veterinary Research, 2023)
Avian influenza virus (AIV) poses a serious problem among poultry production sector, low pathogenic avian influenza H9N2 (LPAI H9N2) has been widely spread globally inducing indirect huge economic losses and it considered as a hidden threaten due to its immunosuppressive impact on birds. Therefore, the current work objectives were the molecular detection of the circulating AI H9N2 field strain in Egypt during 2022-2023 with pathogenicity testing of the recovered virus in specific pathogen free (SPF) one day old chicks. Out of 10 suspected tracheal samples that have been collected from different broiler chicken farms in Al Qalyubia governorate only 7 (70%) samples were positive by Reverse transcription Polymerase chain reaction (RT-PCR). The strain that showed a high reproductive ability and high egg infective dose 50 (EID50) (109/ µl) on ECE via allantoic sac has been selected for pathogenicity testing in SPF chicks. For pathogenicity testing, 60 SPF chicks were allocated into two groups 30 birds each. G1and G2 were inoculated via oculo-nasal route with 100µl containing 1x 106 EID50/ µl virus and 100µl sterile normal saline, respectively. During the experimental time (15 days), no mortalities were recorded in the two groups. The observed clinical signs were mild (ruffled feathers, and depression) in G1, but no clinical signs were observed in G2. During the experiment 3 birds per group were ethically slaughtered to observe the postmortem (PM) and histopathological lesions at 3, 5, 7, 10 and 14 days post-infection (dpi). The observed PM lesions were mild tracheitis, mild pneumonia, subcapsular hemorrhage in liver, enlargement of the spleen, mild atrophy in the pancreas, hemorrhage in the thymus, severe nephritis, and nephrosis with distended ureters with ureates but no macroscopic lesions were detected in the bursa of Fabricius. The virus tropism not restricted only to respiratory, renal, and gastrointestinal tract, but also to the liver, pancreas, and thymus. In conclusion, continuous molecular detection, with pathogenicity testing of circulating AIV is recommended. The authors recommend further full H9 sequence to perform cladogram to the currently tested strain.